Rituximab-augmented myeloablation for first-line autologous stem cell transplantation for mantle cell lymphoma: effects on molecular response and clinical outcome - Dreger, Peter; Rieger, Michael; Seyfarth, Bärbel; Hensel, Manfred; Kneba, Michael; Ho, Anthony Dick; Schmitz, Norbert; Pott, Christiane (Haematologica, the hematology journal, 2007)
Background and Objectives Autologous stem cell transplantation (ASCT) is effective in mantle cell lymphoma (MCL). We investigated whether incorporation of rituximab into the high-dose regimen might further improve the results of ASCT in patients with MCL.Design and Methods In a prospective phase II study, patients with newly diagnosed MCL were treated with a sequential dose-escalating therapy comprising standard chemotherapy for remission induction, intensive ara-C-containing chemotherapy for mobilization of stem cells, and myeloablative therapy followed by ASCT. The myeloablative regimen consisted of total body irradiation and high-dose cyclophosphamide supplemented with two doses (375 mg/m3) of rituximab. Outcome parameters (toxicity, clinical and molecular response as assessed by allele-specific IGH real-time quantitative polymerase chain reaction (RQ-PCR), event-free survival, and overall survival) were compared with those of 34 historical controls treated identically but without rituximab.Results Thirty-four patients were accrued. Whereas engraftment, toxicity and clinical response were not different from those in controls, event-free survival was significantly increased with rituximab (not reached vs. 43 months; hazard ratio 0.38; p=0.036). This was associated with a trend for a superior molecular response rate in 11 study vs. 10 control patients with a marker available (73% vs. 30%, p=0.086) despite similar levels of lymphoma contamination of the stem cell inocula infused.Interpretation and Conclusions Incorporation of two standard doses of rituximab into the myeloablative regimen might improve outcome of upfront ASCT for MCL, allowing long-term disease control to an extent previously not reached in this disease.